(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2025)
Embedded insurance is an innovative approach that integrates insurance coverage directly into the purchase process of goods and services, making it more accessible and convenient for consumers. Global markets are experiencing rapid growth in this sector due to advancements in artificial intelligence, big data, and fintech collaborations. In Uzbekistan, the adoption of embedded insurance remains limited due to outdated regulations, low consumer awareness, and insufficient digital infrastructure. However, the expanding digital financial ecosystem presents significant opportunities for development. Implementing embedded insurance in Uzbekistan could enhance financial inclusion, streamline insurance distribution, and improve market efficiency.